Evaluation of a Model of Transition-Related Instruction to Enhance Self-Directed Career Development of Students with Intellectual and Developmental Disabilities - Yu-Chi Chou (International Journal of Social Sciences and Artistic Innovations)
This study was conducted to investigate the effectiveness of a transition-related instructional model (TRIO) for students with intellectual and developmental disabilities (IDD). The model promoted self-directed problem-solving concerning transitionrelated goals and career development. The TRIO model contained three instructional phases for problem-solving. Throughout the three phases, three essential elements were determined in the transition curriculum for the self-directed learning process, including transition-specific curriculum, self-determination instructions, and the circle of support. 79 junior high school students participated in this study doing group assignments. They were split into the experimental group (n = 36) with the TRIO instruction and the control group (n = 43). Scores on the Career Planning and Development Questionnaire before and after the intervention were analyzed. The results indicated that the experimental group showed significantly higher scores than the control group on the overall career competency and each sub-domain, and the patterns of score change were different between the experimental and control groups when applying the hierarchical linear model (HLM).